THE ARMENIAN ISSUE IN ALBAYRAK AND IRADE-I MILLIYE NEWSPAPERS - UCA, Alaattin; ÇETİNKAYA , Selcen (SSD Journal, 2022)
The Ottoman Empire was a multinational state. Armenians also benefited from the Ottoman Empire’s management style based on tolerance. Turkish-Armenian relations and the Armenian issue are a very comprehensive issue and this issue was published in two newspapers that were the voice of the years of national struggle; It appears frequently in Albayrak and İrade-i Milliye Newspapers.Albayrak Newspaper published 93 issues on March 14, 1913 and March 29, 1915 in Erzurum during the days when Turkish lands were occupied, but 2 of these 93 issues have survived to the present day. The second time the newspaper started its publication life, when the country began to be occupied by the enemy after the Armistice of Mondros; It was dated March 5, 1919 and was published until February 14, 1921. İrade-i Milliye Newspaper started its publication life in Sivas on 4 September 1919 at the end of Sivas Congress and was published until 24 May 1921. Mustafa Kemal Atatürk followed the newspaper closely. These two newspapers carry the characteristics of announcing the occupations of the country, the injustices and the things that need to be said, being the voice of the country and defending the Turkish liberation struggle. In this study, news, articles and articles about the Armenian issue in Albayrak and İrade-i Milliye newspapers were examined.